Un análisis científico-tecnológico de la investigación-acción - Vera Vila, Julio (Teoría de la Educación. Revista Interuniversitaria, 2009)
In this paper, the author studies the action-research in relation to scientifical and technological research. Usually both have been shown as two proposals set against each other. The author recognizes the important contribution done by the action-research, how usefull are its proposals about qualitative methods and teacher’s roi as an intellectual, who takes part in the design of his practice and thinks critically about the process. But from his point of view there are reasons in order to see the accion-research as a scientific-technological pattern. So, education should be looked as a technological practice based on a scientific theory.